Booklet Nutrisi Meningkatkan Asupan Makan dan Kadar Albumin pada Pasien Bedah yang Berisiko Malnutrisi - Ida Mardalena; Umi Istianah; Heru Sucipto; Etik Ratnaningsih (Alma Ata University Press, 2017)
Malnutrition in patients in the hospital have to know anything to do with the increase in the old days of hospitalisation, clinical conditions change, the increased use of hospital resources support, and increased risk of complications. The high malnutrition in hospitals have also been widely reported, at the time of going home from the hospital an average weight loss of 5.4%. In Indonesia, the prevalence of malnutrition is still relatively high, the prevalence of malnutrition by 40% -60% of patients digestif malnutrition. The results of the study in 2007, using the parameters Subjective Global Assessment (SGA), Body Mass Index (BMI), haemoglobin, hematocrit and albumin found the prevalence of malnutrition by 52%, 15%, 55%, 26% and 93%. Research in the UK found that promotional text messages to monitor the weight in the community have helped to identify the risk of malnutrition. Research purposes. This study aims to determine the effect of the use of nutrition booklet on food intake and levels of albumin surgical patients. Research methods. This study uses a pure experiment with Post Test Only with Control groups Design. Involved 60 respondents were divided into treatment group and 30 respondents 30 respondents comparison group. Statistical test using independent t-test with CI 95% Results: There were significant differences average remaining meal among surgical patients who use the nutrition booklet that does not use a nutrition booklet on alpha 5% with the p-value of 0.03. There are differences in the average value of serum albumin among surgical patients who use the nutrition booklet that does not use a nutrition booklet on alpha 5%, p 0.0001. Serum albumin levels and food intake increased significantly with the use of nutritional booklet.